The concept of court and its most crucial aims in Quran (Raparin Journal of Humanities (RJH), 2024)
It can be said that judicature is a settlement of a conflict between two opponents by the law of quran. while filing a complaint with a judge to those who organizers yhat the judge and opponent must keep to in the trail process. The judicature has many meanings in Quran. the most important meanings are first،ordering and completing worship،ruling acting fulfilling commands completely and end the obstacles among people and insisting on things. another one is promise and the will all meanings mean ending problems. The court is a terrible mandate. no one can give rights apart from those who know and act on them. in the judicature، there are several targets، including the showing and explosure the rights،the settlement of disputes، removable of oppression ، and reconciliation between people and also imposition of limits.